Cyclization-activated prodrugs - Paula Gomes (2007)
Many drugs suffer from an extensive first-pass metabolism leading to drug inactivation and/or production of toxic metabolites, which makes them attractive targets for prodrug design. The classical prodrug approach, which involves enzyme-sensitive covalent linkage between the parent drug and a carrier moiety, is a well established strategy to overcome bioavailability/toxicity issues. However, the development of prodrugs that can regenerate the parent drug through non-enzymatic pathways has emerged as an alternative approach in which prodrug activation is not influenced by inter- and intraindividual variability that affects enzymatic activity. Cyclization-activated prodrugs have been capturing the attention of medicinal chemists since the middle-1980s, and reached maturity in prodrug design in the late 1990s. Many different strategies have been exploited in recent years concerning the development of intramoleculary-activated prodrugs spanning from analgesics to anti-HIV therapeutic agents. Intramolecular pathways have also a key role in two-step prodrug activation, where an initial enzymatic cleavage step is followed by a cyclization-elimination reaction that releases the active drug. This work is a brief overview of research on cyclization-activated prodrugs from the last two decades.